Pengaruh Akuntabilitas, Transparansi, dan Partisipasi Masyarakat Terhadap Pengelolaan Alokasi Dana Desa Studi Kasus Pada Pemerintah Desa Kecamatan Gantarang Kab.Bulukumba Provinsi Sulawesi Selatan - Asmaul Husna; Sri Rahayu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study was conducted to determine whether accountability, transparency and community participation have an influence on the Gantarang District Village Government in 2020 either simultaneously or partially. This study uses multiple linear regression techniques. This research is included in descriptive research and is a clause in nature. The population in this study is the Village Government of Gantarang District. Sampling in this study used a non-probability sampling technique with a saturated sampling method so that 90 respondents were obtained from all village officials in the Gantarang District Village Government. The results of the study show that simultaneously accountability, transparency, and community participation affect the management of village fund allocations in the Gantarang District Village Government in 2020. While partially shows that accountability, transparency, and community participation have a significant positive effect on the management of village fund allocations in Gantarang District Village Government in 2020